The Code is not Coloured - Martin, John (2011)
While discussing my master degree research, my mother reminded me that my one-time art dealer Ray Hughes said I should paint a few good pictures rather than hundreds. My reply was, “As a maximalist, I’ve never done anything that way.” This approach is not original. In 1807, English polymath Thomas Young published A Course of Lectures on Natural Philosophy and the Mechanical Arts attempting to outline all knowledge of his time. In the historical section of Zur Farbenlehre, published in 1810, German poet and scientist Johann Wolfgang von Goethe attempted to outline all the known theories of colour. Then in 1988, Dennis Sepper described Goethe’s colour science methodology as “naive induction”.